2015
DOI: 10.5539/gjhs.v8n6p41
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association Between rs17568 Polymorphism in OX40 Gene and Myocardial Infarction, Southern of Iran

Abstract: Tumor necrosis factor (TNF) is one of the inflammatory cytokines which has an important role in inflammation and migration of other inflammatory cells to the atherosclerotic plaques. OX40 is a member of the TNF super family receptor protein. OX40 and OX40 ligand are co-stimulators for T-cells and can increase inflammatory response in atherosclerotic plaques. The aim of this study was to determine the association of rs17568 polymorphism in OX40 gene with premature myocardial infarction. This case control study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…A total population of 763 individuals (aged 43.6 ± 5.77 years, mean ± SD) was included in the meta‐analysis. The definition of dyslipidaemia in various studies was as follows: Total cholesterol > 250mg/dL, LDL > 160 mg/dL or on lipid‐lowering therapy According to NCEP guidelines Total cholesterol ≥ 200 mg/dL or HDL < 40 mg/dL Total cholesterol > 200mg/dL, LDL > 130 mg/dL or triglycerides > 200 mg/dL and One study mentioned no description for dyslipidaemia …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total population of 763 individuals (aged 43.6 ± 5.77 years, mean ± SD) was included in the meta‐analysis. The definition of dyslipidaemia in various studies was as follows: Total cholesterol > 250mg/dL, LDL > 160 mg/dL or on lipid‐lowering therapy According to NCEP guidelines Total cholesterol ≥ 200 mg/dL or HDL < 40 mg/dL Total cholesterol > 200mg/dL, LDL > 130 mg/dL or triglycerides > 200 mg/dL and One study mentioned no description for dyslipidaemia …”
Section: Resultsmentioning
confidence: 99%
“…Descriptive characteristics of studies Total cholesterol ≥ 200 mg/dL or HDL < 40 mg/dL 28 • Total cholesterol > 200mg/dL, LDL > 130 mg/dL or triglycerides > 200 mg/dL 25 and • One study mentioned no description for dyslipidaemia 32. …”
mentioning
confidence: 99%
“…Eight publications were excluded because there were no data for rs3850641 or rs17568 polymorphisms, were unavailable to raw data, or were about other polymorphisms. Finally, a total of 11 publications ( 20 - 30 ) were included. For TNFSF4 rs3850641 polymorphism, a total of nine publications with 11 case-control studies comprising 3,865 cases and 6,344 controls were included, whereas three publications with three case-control studies comprising 785 cases and 698 controls were included for rs17568 polymorphism.…”
Section: Resultsmentioning
confidence: 99%
“…Among these findings, TNFSF4 was newly found to be related with the risk of cardiovascular and cerebrovascular diseases ( 1 - 7 ). Several studies have showed the relationship between TNFSF4 polymorphisms and the risk of CHD and stroke, but contradictory findings were observed ( 21 - 30 ). Among all polymorphisms under investigation, rs3850641 gained more attention than others.…”
Section: Discussionmentioning
confidence: 99%